Julio De Zan: Dialectics, Militarism and a new form of Heteronomy - Del Valle, Alejandro (2021)
From the standpoint of the relation between theory and practice, this work address the relation established by De Zan between the dialectical method and a form of praxis which, from the framework of the classic strategic thought, we defined as militarism. This work try to highlight the intellectual procedure through which theoretical-practical equivalences are established among the dialectical method and the militarism and how this intellectual procedure underpin a critic against the Marxism. As conclusion we present a critical argument in order to question the linkage established by De Zan and we value the particular content that the notion of heteronomy take from the perspective of the philosophy of liberation.